1949
DOI: 10.1021/ac60031a006
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Recording of Polarographic Data Obtained with Platinum Electrodes

Abstract: equalizing valve was opened, these fluctuations all but vanished; the remaining noise was attributed to the position indicator.The utility of the analyzer for continuous measurements over extended periods was impaired by the persistence of drift, which made it necessary to recenter the drop from time to time by momentarily opening the equalizing valve on the detector. The direction and magnitude of the observed drift were variable and may have been caused by slow changes in the source temperature, as compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1950
1950
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…The appearance of maxima on the polarographic curves obtained with the rotating platinum electrode has been reported. 19 In the preliminary investigations into the best set of operating conditions, we also observed maxima. In general these were found to be due to (i) incomplete cleaning of the cathode, (ii) too great a rate of voltage scanning, (iii) too small an anode.…”
Section: Maximamentioning
confidence: 64%
“…The appearance of maxima on the polarographic curves obtained with the rotating platinum electrode has been reported. 19 In the preliminary investigations into the best set of operating conditions, we also observed maxima. In general these were found to be due to (i) incomplete cleaning of the cathode, (ii) too great a rate of voltage scanning, (iii) too small an anode.…”
Section: Maximamentioning
confidence: 64%
“…On the basis of the earlier findings of Rogers and co-workers (9)(10)(11)(12)(13)(14)(15)(16)(17), the adsorption of metal ions on foreign substrates was studied experimentally and theoretically in many systems by Schmidt and co-workers in the last decade . They develc>ped new experimental techniques in order to determine exactly the thermodynamics of metal ion adsorption processes and the formation of metal films.…”
Section: Eiectrochem Soc: Electrochemical Science and Technologymentioning
confidence: 99%
“…It was only relatively recently that it was found that certain amounts of metal are being deposited at potentials well anoxic to the reversible potential [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The earliest explanation [11] of this phenomenon argued that the small number of lattice sites on the electrode have adsorption energies for metal atom deposition so high as to be equal to the substrate work function, the rest of the sites available being associated with adsorption energies smaller than this.…”
Section: Introductionmentioning
confidence: 99%